Sexual and gender minority health - LeBlanc, Allen J.; Perry, Brea L. (Emerald Publishing Limited, 2021)
Research concerning sexual and gender minority (SGM) health has flourished in recent years in conjunction with a period of intense social, political, and legal discourse about SGM persons. While this attention has increased understanding and recognition of SGM experiences, recent advances have often been met with resistance and backlash rooted in social stigma and long histories of discrimination. This volume of Advances in Medical Sociology showcases rich theoretical and empirical contributions on SGM health and wellbeing. The chapters address a variety of topics, drawing from classic and contemporary sociological frameworks and constructs, and reflecting intersecting interdisciplinary approaches to SGM health. Research presented in this volume provides an in-depth focus on sexual and/or gender minority populations, as well as the diverse sub-populations within them; theoretical and empirical explanations for SGM health disparities and resilience; aging and life course perspectives on the health experiences of SGM persons; health in the context of critical relationships in the lives of SGM persons; and the experiences of seeking general and specialized health care among SGM. The time is ripe for deeper examinations of the social determits of SGM health, and this volume seeks to begin filling existing gaps in the literature.
Includes index.
Keywords: Sexual minorities -- Health and hygiene.; Health & Fitness, Sexuality.; Popular medicine & health.; elektronické knihy; electronic books